ANALYSIS OF THE VALIDITY OF MULTIPLE-CHOICE TEST ITEMS ON MASTERY OF TEMPERATURE AND HEAT CONCEPTS FOR SENIOR HIGH SCHOOL STUDENTS (SMA) - Ummah, Jamiatul; Sutopo, Sutopo; Mufti, Nandang; Ardilla, Sarah Lutfiah (Jurnal Pendidikan Matematika dan IPA, 2026)
This study aims to examine a test instrument to ensure its conformity with appropriate formats and procedures for measuring senior high school students’ mastery of temperature and heat concepts. The instrument consists of 14 multiple-choice questions. This study uses a quantitative descriptive method to evaluate and produce a high-quality and valid test instrument. The instrument underwent revision through consultation with expert lecturers and was then empirically tested on 95 students at SMAN 1 Pamekasan as respondents. The test items were analyzed using SPSS version 30, covering four stages of empirical analysis: validity testing, reliability testing, item difficulty analysis, and item discrimination analysis, all conducted using classical test theory parameters. Based on the results of the point biserial analysis, questions 1, 9, and 11 are below standard. Reliability shows a Cronbach's alpha of 0.708, which means it is reliable. The difficulty level test results show that out of 14 questions, 3 questions are categorized as difficult and 1 question is very easy. In the discrimination test, 5 questions are categorized as poor, 3 questions are moderate, and 7 questions are good. Overall, 11 questions were deemed acceptable and passed the empirical test, while 3 questions (numbers 1, 9, and 11) were disqualified. The weakness of this instrument testing is that the results are highly dependent on the abilities of the participants. For example, question number 9, which was adapted from PhysPort and simplified in language, still had to be disqualified because it did not meet the empirical criteria.